The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.chest.2021.01.057
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes and Subphenotypes of Patients With COVID-19

Abstract: BACKGROUND: Since COVID-19 was identified, its clinical and biological heterogeneity has been recognized. Identifying COVID-19 phenotypes might help guide basic, clinical, and translational research efforts.RESEARCH QUESTION: Does the clinical spectrum of patients with COVID-19 contain distinct phenotypes and subphenotypes? STUDY DESIGN AND METHODS: We included adult patients ($ 18 years) positive for laboratory-confirmed SARS-CoV-2 infection from a prospective COVID-19 registry database in the Cleveland Clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 24 publications
1
33
0
Order By: Relevance
“…Sepsis and ARDS represent umbrella syndromes containing multiple subphenotypes with relatively distinct clinical or biological signatures and differing outcomes 2 , 3 . Using latent class analysis, similar findings have also been applied to large population cohorts with COVID-19 4 , 5 . Currently, only one small study of 18 patients hospitalised with COVID-19 has focused on hyperlactataemia but did not report associations with the degree of hypoxaemia or vasopressor use 6 .…”
mentioning
confidence: 83%
“…Sepsis and ARDS represent umbrella syndromes containing multiple subphenotypes with relatively distinct clinical or biological signatures and differing outcomes 2 , 3 . Using latent class analysis, similar findings have also been applied to large population cohorts with COVID-19 4 , 5 . Currently, only one small study of 18 patients hospitalised with COVID-19 has focused on hyperlactataemia but did not report associations with the degree of hypoxaemia or vasopressor use 6 .…”
mentioning
confidence: 83%
“…To date, studies aiming to derive phenotypes of hospitalized COVID-19 patients have been based on previous comorbidities, 6 , 7 , 8 , 15 COVID-19 signs and symptoms, 8 , 9 , 11 , 12 , 16 , 17 variables from blood tests, 8 , 11 , 13 , 14 , 15 , 16 , 17 and chest radiologic features 8 , 10 in an attempt to identify groups of patients with distinct risks of ICU admission, need for mechanical ventilation, and risk of experiencing clinical complications or death. Among those focused on critically ill patients, 11 , 12 , 13 , 14 , 15 , 16 , 17 most studies identified two or three phenotypes corresponding to different degrees of severity with a role of intense inflammation when defining the most severe phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies have aimed to identify phenotypes among hospitalized COVID-19 patients based on sociodemographic variables, baseline comorbidities, signs and symptoms during the acute phase, and the results of complementary tests, such as biological parameters in the blood test 6 , 7 , 8 , 9 or chest radiological features. 8 , 10 Most interestingly, several studies have focused on patients admitted to the ICU that are those at a higher risk of experiencing severe complications and sequelae.…”
Section: Introductionmentioning
confidence: 99%
“… RESEARCH QUESTION: Does the clinical spectrum of patients with COVID-19 contain distinct phenotypes and subphenotypes? ” 19 …”
Section: Examples Of Research Questions From Published Articlesmentioning
confidence: 99%